STUDI PENDAHULUAN PENGEMBANGAN MODUL PEMBELAJARAN EKOSISTEM DENGAN PENDEKATAN PROBLEM-BASED LEARNING (PBL) DAN INTEGRASI LITERASI NUMERASI UNTUK SMA/MA - Rafdina, Aisyah; Ardi, Ardi (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to develop a learning module that integrates Problem-Based Learning (PBL) and numeracy literacy for understanding ecosystem concepts among high school students. Data obtained through initial observations using preliminary questionnaire sheets for teachers and students. A more in-depth learning approach is needed in developing students' numeracy literacy skills to improve their ability to utilize reading and data and numbers effectively in biology materials. As many as 86.2% of students agree that the learning module is the most appropriate media to support the learning process. From this, it can be concluded that it is necessary to develop a learning module for ecosystem material with the Problem-Based Learning (PBL) Approach and Numeracy Literacy Integration for phase E.